CEO Compensation and Stakeholders' Claims* - ARORA, ALKA; ALAM, PERVAIZ (Contemporary Accounting Research, 2005)
Abstract The traditional view that a corporation exists solely to serve the interests of the firm's shareholders has given way to a changing view that recognizes the importance of corporate constituents in addition to shareholders. Prior studies demonstrate a significant association between the sensitivity of CEO compensation and a firm's stock prices. However, the association between CEO compensation and the claim of other primary stakeholders (customers, employees, suppliers) has not been examined. The purpose of this study is to investigate whether the adoption of long‐term incentive plans aligns the interest of the CEO with the interest of the primary stakeholders in the firm. Using the fixed‐effect regression, our results indicate a significant association between the change in CEO compensation and the claims of the customers, shareholders, and employees. We contribute to the literature by demonstrating that the managers are accountable not only to the shareholders but also to primary stakeholders.